Reachability Problems 7th International Workshop, RP 2013, Uppsala, Sweden, September 24-26, 2013 Proceedings - Abdulla, Parosh Aziz.; Potapov, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 7th International Workshop on Reachability Problems, RP 2013, held in Uppsala, Sweden, in September 2013. The 19 revised papers (The 14 revised papers were carefully reviewed and selected from 24 submissions in addition to 5 invited talks) were carefully reviewed and selected from 24 submissions. Topics of interest include reachability for finite state systems; rewriting systems, reachability analysis in counter/timed/cellular/communicating automata; Petri-nets; computational aspects of semigroups, groups and rings; reachability in dynamical and hybrid systems; frontiers between decidable and undecidable reachability problems; complexity and decidability aspects, predictability in iterative maps and new computational paradigms.
Reachability for finite state systems -- Rewriting systems, reachability analysis in counter/timed/cellular/communicating automata -- Petri-nets -- Computational aspects of semigroups, groups and rings -- Reachability in dynamical and hybrid systems -- Frontiers between decidable and undecidable reachability problems -- Complexity and decidability aspects, predictability in iterative maps and new computational paradigms.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices